Rectangular rigid stamp on a nonlocal elastic half-plane - Reha, Artan; Tanju, Yelkenci (Elsevier BV, 1996)
First, the solution of the problem of a rectangular rigid stamp uniformly moving on an elastic half plane is given. Secondly, the solution is obtained for a motionless rectangular stamp on a nonlocal elastic half space. The finite distribution of the stress under the stamp has been compared with the unbounded stresses of local case.
Keywords: Nonsimple materials; Theories of friction (tribology); Contact in solid mechanics